Improving the Deodorizing Ability of Cotton Fabric by Printing with Bamboo Charcoal. Issue 1 (31st December 2023) - Vuthiganond, Nattaya; Nakpathom, Monthon; Somboon, Buppha; Narumol, Nootsara; Mongkholrattanasit, Rattanaphol
ABSTRACT: Due to its relatively large specific surface area and microporous structure, bamboo charcoal is widely employed in a variety of industries, including the textile sector. In this investigation, bamboo charcoal powder was formulated as a natural colorant in the pigment print paste and then applied to cotton fabric by screen printing. Colorimetric values were assessed and color fastness to washing, light, and crocking as well as mechanical properties was performed according to related standards. By varying the amount of bamboo charcoal, the printed fabric had a light to dark gray color with good to excellent wash, light, and crock fastness. The combination of binder and fixing agent in the print paste increased fabric tensile strength, elongation, tear strength, and more pronounced stiffness. Besides, the bamboo charcoal printed cotton exhibited a deodorizing rate of 80.3–87.8% against ammonia gas after 40 min and was maintained at 54.8–73.1% after 10 washing cycles.